Suppressing Efficiency Roll-Off of TADF Based OLEDs by Constructing Emitting Layer With Dual Delayed Fluorescence - Zhang, Yuewei; Li, Zhiqiang; Li, Chenglong; Wang, Yue (Frontiers in Chemistry, 2019)
To suppress efficiency roll-off induced by triplet−triplet annihilation (TTA) and singlet−triplet annihilation (STA) in thermally activated delayed fluorescence (TADF) based organic light emitting diodes (OLEDs) is still a challenge. This issue was efficiently addressed by generating dual delayed fluorescence in the emitting layer of OLEDs. A novel TADF compound, PXZ-CMO, featuring a D-A structure was designed and synthesized. By dispersing the emitter into different hosts, devices G1 (MCP host) and G2 (DPEPO host) with identical configurations were carefully fabricated, which showed similar maximum EQE / CE of 12.1% / 38.2 cd A−1 and 11.8% / 33.1 cd A−1, respectively. Despite severe efficiency roll-off in device G2 with only 6.4% EQE remaining at a luminance of 1000 cd m−2, a remarkably reduced efficiency roll-off was attained in device G1, retaining EQE as high as 10.4% at the same luminance of 1000 cd m−2. The excellent device performance with reduced roll-off in device G1 should result from the dual delayed fluorescence in the emitting layer, which possesses great advantages in achieving dynamic and adaptive exciton distribution for radiation acceleration and quench suppression.